TUAN TABAL (M. 1891) DAN SUMBANGANNYA DALAM PERKEMBANGAN ISLAM DI TANAH MELAYU - Berahim@Ibrahim, Ahmad Zaki; Mohd Nor, Mohd Roslan (Journal of Al-Tamaddun, 2009)
Tuan Tabal is one of the Muslim scholars in Malay Archipelago. He has hugely contributed to the development of Islam in this area especially in the field of Islamic Studies. This paper will attempt to focus on and explore his contribution in spreading Islam in Malay Archipelago.